Design of a focused collimator for proton therapy spot scanning using Monte Carlo methods. Issue 7 (6th April 2020) - Geoghegan, Theodore J.; Nelson, Nicholas P.; Flynn, Ryan T.; Hill, Patrick M.; Rana, Suresh; Hyer, Daniel E.
Abstract : Purpose: When designing a collimation system for pencil beam spot scanning proton therapy, a decision must be made whether or not to rotate, or focus, the collimator to match beamlet deflection as a function of off‐axis distance. If the collimator is not focused, the beamlet shape and fluence will vary as a function of off‐axis distance due to partial transmission through the collimator. In this work, we quantify the magnitude of these effects and propose a focused dynamic collimation system (DCS) for use in proton therapy spot scanning. Methods: This study was done in silico using a model of the Miami Cancer Institute's (MCI) IBA Proteus Plus system created in Geant4‐based TOPAS. The DCS utilizes rectangular nickel trimmers mounted on rotating sliders that move in synchrony with the pencil beam to provide focused collimation at the edge of the target. Using a simplified setup of the DCS, simulations were performed at various off‐axis locations corresponding to beam deflection angles ranging from 0° to 2.5°. At each off‐axis location, focused (trimmer rotated) and unfocused (trimmer not rotated) simulations were performed. In all simulations, a 4 cm water equivalent thickness range shifter was placed upstream of the collimator, and a voxelized water phantom that scored dose was placed downstream, each with 4 cm airgaps. Results: Increasing the beam deflection angle for an unfocused trimmer caused the collimated edge of the beamlet profile to shift 0.08–0.61 mm from the baseline 0° simulation. There was also an increase in low‐dose regions on the collimated edge ranging from 14.6% to 192.4%. Lastly, the maximum dose, D max, was 0–5% higher for the unfocused simulations. With a focused trimmer design, the profile shift and dose increases were all eliminated. Conclusions: We have shown that focusing a collimator in spot scanning proton therapy reduces dose at the collimated edge compared to conventional, unfocused collimation devices and presented a simple, mechanical design for achieving focusing for a range of source‐to‐collimator distances. Abstract :